2007
DOI: 10.1038/sj.onc.1210259
|View full text |Cite
|
Sign up to set email alerts
|

Frequent epigenetic inactivation of SFRP genes and constitutive activation of Wnt signaling in gastric cancer

Abstract: Activation of Wnt signaling has been implicated in gastric tumorigenesis, although mutations in APC (adenomatous polyposis coli), CTNNB1 (b-catenin) and AXIN are seen much less frequently in gastric cancer (GC) than in colorectal cancer. In the present study, we investigated the relationship between activation of Wnt signaling and changes in the expression of secreted frizzled-related protein (SFRP) family genes in GC. We frequently observed nuclear b-catenin accumulation (13/15; 87%) and detected the active f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
184
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 204 publications
(198 citation statements)
references
References 38 publications
14
184
0
Order By: Relevance
“…Although it is well known that mutation in APC, CTNNB1 and AXIN is infrequent in GC, we found that the majority of GC cells showed activation and nuclear accumulation of b-catenin and methylation of multiple SFRP genes (Nojima et al, 2007). Among those GC cells, only a few cell lines in which APC or CTNNB1 was mutated showed significant upregulation of TCF/LEF transcriptional activity (Nojima et al, 2007).…”
Section: Genetics and Genomicsmentioning
confidence: 66%
See 4 more Smart Citations
“…Although it is well known that mutation in APC, CTNNB1 and AXIN is infrequent in GC, we found that the majority of GC cells showed activation and nuclear accumulation of b-catenin and methylation of multiple SFRP genes (Nojima et al, 2007). Among those GC cells, only a few cell lines in which APC or CTNNB1 was mutated showed significant upregulation of TCF/LEF transcriptional activity (Nojima et al, 2007).…”
Section: Genetics and Genomicsmentioning
confidence: 66%
“…We previously reported that three of the five SFRP genes (SFRP1, SFRP2 and SFRP5) were frequently methylated and silenced in CRC and GC cells (Suzuki et al, 2002;Nojima et al, 2007). For that reason, in the present study we initially evaluated the expression status of SFRP1, SFRP2 and SFRP5 in a panel of breast cancer cell lines.…”
Section: Analysis Of Wnt Antagonist Gene Expression In Breast Cancer mentioning
confidence: 98%
See 3 more Smart Citations